Features wear nodes mechanization wing aircraft operating under dynamic loads - Хімко, А.М.; Якобчук, О.Є.; Бородій, В.М.; Задніпровська, С.М.; Холод, Н.В. (Proceedings of National Aviation University (archive), 2009)
The conducted researches of titanic alloy ВТ-22 at dynamic loading with cycled sliding and dynamic loading in conditions of rolling with slipping. It is established that roller jamming in the carriage increases wear of rod of mechanization of a wing to twenty times. The optimum covering for strengthening wearied sites and restoration of working surfaces of wing’s mechanization rod is defined.